Underpreparedness in South African higher education: A limited test of the English grammar awareness of first-year students - Moyo, J. (South African Journal of Higher Education, 2020)
This quasi-experimental study, limitedly, explores the level of English grammar awareness as a potential partial indicator of “underpreparedness” in a population of first-year students doing an English for Academic Purposes (EAP) module in a South African university. This is done by comparing the mean test scores and linguistic errors in two slightly different but equivalent parts-of-speech grammar test components in the assignment and supplementary examination scripts of two naturally-occurring subpopulations of the EAP population. Members of the EAP population were in the tests required to correct authentic text parts that had been morphologically and syntactically corrupted for correction. The statistical and linguistic error analyses returned a higher mean test score and a bigger correct-incorrect response ratio for the assignment script sample (the A-Sample) than for the supplementary examination script sample (the SE-Sample). These results suggested, firstly, that extraneous variables were responsible for the variation in the sample test performances, and, secondly, that the grammar instruction, testing and error correction treatments had probably had negligible to no effect at all. The error analysis points to the inadvisability of the inclusion of peripheral grammatical categories such as adverbs in textual modifications for editing as they may not offer optimal opportunities for the exploitation for instructional purposes of the meaning potential of syntactic structures. The grammar instruction observation data showed that a majority of the SE-Sample participated with apparent interest and enthusiasm, thereby suggesting that they viewed the grammar instruction as useful. The observation data also contained a case of resistance to grammar instruction by an older student with a different background to the majority EAP population.